Titanium dioxide-carbon spheres composites for use as supports in cobalt Fischer-Tropsch synthesis - Phadi, Thabiso Terence (My University, 2013)
Fischer-Tropsch (FT) synthesis is a reaction which entails the conversion of synthesis gas, also known as syngas (a mixture of H2 and CO gases), to liquid hydrocarbon fuels, oxygenated hydrocarbons, chemicals and water. This syngas mixture is obtained from natural gas, coal, petroleum, biomass or even from organic wastes. In this study cobalt catalysts supported on novel carbon spheretitania (CS-TiO2) composite materials were synthesized and tested for their performance in the FT process. Initially carbon spheres (d = 80-120 nm) were prepared in a vertical swirled floating chemical vapour deposition reactor without the use of a catalyst. The rate of production was controlled and the highest production rate of about 195 mg/min was obtained at an acetylene (C2H2) flow rate of 545 mL/min at 1000 °C. The produced carbon spheres (CSs) had a narrow size distribution with a uniform diameter size. Purification and functionalisation of the CSs improved the total surface area, due to the removal of PAHs which blocked the CS pores. The introduction of functional groups to the CSs was achieved and these changed the wetting properties of the CSs. Functionalising the CSs for longer than 17 h in HNO3 destroyed the morphology of the CSs. After successful preparation of functionalised CSs, the interactions between CSs and TiO2 were studied by in the TiO2 composite using two different sol-gel methods, namely the conventional sol-gel and the surfactant wrapping sol-gel method. The surfactant wrapping sol-gel method entailed the modification of the CSs by dispersing them in a surfactant, in this case hexadecyltrimethylammonium bromide or CTAB [(CH3(CH2)15N(CH3)3Br]. This introduced alkyl “tails” which eased the dispersability of the CSs before coating them with Ti[O(CH2)3CH3]4 (a source of TiO2) to produce a homogeneously coated CS-TiO2 composite material (defined as ASW3). It should be mentioned that many, many experiments were performed to develop an efficient and reliable method to make homogeneously coated CS-TiO2 composites since it was found to be very difficult to achieve an interaction between carbonaceous materials and TiO2 especially by sol-gel procedures. The traditional sol-gel method was used to prepare CS-TiO2 composites with different ratios viz. 1CS-1SG, 1CS-2.5SG, 1CS-5SG, 1CS-10SG, 1CS-25SG and 1CS-50SG. These composites showed weak interactions between CSs and TiO2 even at high TiO2 loading ratio. Interestingly the surface area of these composites showed high values of 80 and 85 m2/g for 1CS-5SG and 1CS-10SG, respectively. At lower TiO2 ratios the measured surface area was similar to that of CSs, i.e 10 m2/g for 1CS-1TiO2. At high TiO2 ratios the measured surface area was similar to that of TiO2, i.e 49 m2/g for 1CS-50TiO2. The TEM images of CS-TiO2 (ASW3) composites prepared by surfactant wrapping methods showed a successful TiO2 coating of CSs. The TiO2 grain size was 8.0 nm with both anatase and rutile phases. High surface areas (up to 98 m2/g) of composite materials were achieved by employing this procedure. The high surface areas achieved suggest that the interaction between CSs and TiO2 was homogeneous and the increase was due to the “bridge” formed between CSs and TiO2. A series of cobalt catalysts (10% by weight) supported on these materials was carried out by the deposition precipitation method using Co(NO3)2·6H2O as the metal precursor. After appropriate drying and calcination the catalysts were characterized using traditional characterisation techniques and tested in the FT reaction using a fixed bed reactor. The the 10%Co/CS catalyst produced a CO conversion of 15.2% while the catalyst had a low total BET surface area (6 m2/g) compared to non-carbonaceous catalysts with higher BET surface areas. This observation suggests that the surface area did not necessarily play a role in the CO conversion, but that other properties (reducibility and dispersion) of CSs influenced the catalyst activity. After coating CSs with TiO2 and loading cobalt to produce 10%Co/ASW3 both the BET surface area of the catalyst and the CO conversion increased to 83 m2/g and 20.1%, respectively. CO-TPD of 10%Co/ASW3 showed a large amount of strongly adsorbed CO. This increased CO was due to the interaction between CSs and TiO2 which developed CO adsorptive sites.
Keywords: Fischer-Tropsch process.; Coal liquefaction.; Cobalt catalysts.